Public Finance, Governance, And Growth In Transition Economies : Empirical Evidence From 1992-2004 - Varoudakis, Aristomène A., ca. 20./21. Jh. ca. 20./21. Jh (The World Bank, 2007)
This paper revisits the early empirical literature on economic growth in transition economies, with particular focus on fiscal policy variables-fiscal balance and the size of government. The baseline model uses a parsimonious specification, drawn from Fischer and Sahay (2000), of economic growth as a function of initial conditions, stabilization, liberalization, and structural reform. The paper expands the data used in previous analyses by up to 10 years and finds unambiguous evidence that fiscal balance matters for growth, while confirming other previous findings on the correlates of economic growth in transition economies. In addition, the paper extends the baseline model and explores potential sources of nonlinearities in the relationship between growth and public finance. A key finding is that determinants of growth may vary in relative importance, depending on the underlying institutional quality. The evidence indicates that there could be higher growth payoffs from macroeconomic stability and public expenditure in countries characterized by relatively better public sector governance as measured by relevant indicators. In addition, the size of government matters for growth in a nonlinear manner: Beyond indicative thresholds of expenditure levels, public spending has a negative impact, while at levels below the threshold, there is no measurable impact on economic growth